Funcionamiento económico de los hogares; sus fuentes de bienserestar* y sus recursos - Boltvinik, Julio (El Colegio de México, 2023)
In section one, I define a typology of households and a reproduction scheme for each of the five types of household identified. The reproduction schemes link the three main institutional sectors: households, firms, and government. In section two, these schemes are used to develop the conception of households’ well-being sources (HWBS) as well as their application in the critique of partial poverty measurement methods. Lastly, the HWBS scheme is compared with the resource schemes devised by various authors.